Insect communities inhabiting Inonotus radiatus growing on Alnus glutinosa trees at northern and southern shores of boreal lakes - González Alonso, Clara (2011)
This is a study of the insect community associated to the wood-decaying fungus Inonotus radiatus found on Alnus glutinosa trees growing in riparian forests at the northern and southern shores of boreal lakes in the province Uppland. Little is known about this particular bracket fungus and its inhabitants. Insects were reared out at the laboratory from samples of fruiting bodies of the fungus taken at five lakes. During the fieldwork in 2009, data about several environmental variables was also taken. After the rearing period, these variables and their effects over the insects were analyzed. Special attention is paid to the comparison between the insect communities living at northern and southern shores of the lakes. We consider the microclimates at the northern and southern shores are different due to the dissimilar sun exposure they receive. The collected insect communities associated to opposite shores are not identical, but the variable shore exposition turned out to be influencing just four of the studied taxa. The variables which turned out to have a greater impact over the insect communities were lake, weight of the fungus and sun exposure. The preferences regarding successional stage of the fruiting bodies by some of the collected taxa are also presented. Most of them seem to be more attracted by older fruiting bodies than by the new and fresher ones. One red-listed beetle species has been recorded during the project, as well as three other species which were included in previous Red Lists although they are no longer on the Swedish Red List. Distributions of insect species are also revised to analyze the accuracy of the Red List.